Optimalisasi Pelaksanaan Pergantian Crew Kapal Terhadap Kesesuaian Kontrak Perjanjian Kerja Laut (PKL) Pada PT. Gerbang Samudra Sarana - Priyono, Budi; Agung Samudro, Denni Farobi (Universitas Hang Tuah, 2021)
The management of Human Resources manning the ship which is handled by the manning division, optimization in sea transportation is very important to be done to be more effective, one of which is in terms of changing the crew of the ship, the change of the crew of the ship must be in accordance with the replacement plan that has been prepared by the manning division so that The change goes according to the Sea Work Agreement. The research method used in this research is a qualitative approach with a descriptive research type. Sources of research data were obtained from observations, interviews, and documentation. Analysis of research data was carried out by qualitative analysis. The results of the study indicate that there is a discrepancy in the planned change of ship crew because the company only has trust in the Ex-crew as a replacement ship crew. Ex-crew who had planned to board the ship could not keep their promise to return to the company, so the manning division had to find a new crew, if no new crew recruitment was carried out it would result in a lack of stand-by crew provided by the company causing delays in changing crew sign on /off and crew on board. so that the ship crew must increase the contract period of the Sea Work Agreement until the specified time. Therefore, the contract period for the ship crew on board must be in accordance with the agreement written in the Sea Work Agreement.